Waḥy and tanzīl - Leirvik, Oddbjørn (Studia theologica, 2015)
This article analyses modern discourses about "revelation" in the writings of three Western Orientalists (Muir, Bell and Watt) and of a selection of contemporary Muslim reformists (Fazlur Rahman, Farid Esack, Ibrahim Moosa, Abdelkarim Soroush, Mohammed Arkoun and Nasr Hamid Abu Zayd). After some terminological considerations, the named thinkers' views of revelation are analysed in light of their understanding of the Qur'anic terms waḥy ("inspiration") and tanzīl ("sending down"), which in modern discourses are conventionally associated with the phenomenon of revelation. The author finds that the cited reformists' understanding of revelation and of the terms waḥy and tanzīl may be wedded to (1) an interest in the inspired person, (2) a progressive view of divine communication or (3) an insistence on the human nature of the sacred text. From a hermeneutical perspective, the author suggests that Paul Ricoeur's notion of "the world of the text" may offer a more useful framework for discussing the nexus between divine and human communication than the elusive phenomenological category of revelation.